Applications of Cascaded Multilevel STATCOM Combined with Battery Energy Storage System in Wind Farm - CAO Wei; HAN Yashuai; XU Yonghai (Kongzhi Yu Xinxi Jishu)
Due to the disadvantage of traditional STATCOM for only regulating reactive power, it analyzed the large capacity cascaded multilevel STATCOM combined with energy storage system. The STATCOM consists of battery energy storage system, nonisolated DC/DC converter and cascaded multilevel STATCOM.A coordinated control strategy of STATCOM/BESS applied in wind farm was analyzed. The models of wind farm and STATCOM/BESS were built in PSCAD/EMTDC. The simulation results show that the active power fluctuations of wind farm are effectively smoothed by STATCOM/BESS under steady-state conditions, and certain reactive power can be provided rapidly to system during power grid fault, thus the continuous operation of wind farm can be ensured.